(untitled) (LACCEI, 2024)
This contribution estimates the of Superficial Urban Heat Island Intensity (SUHI) during the period 2001 - 2016 for the Metropolitan Area of ​​Caracas (AMC) and Santiago (AMS), located in Venezuela and Chile respectively. To quantify the SUHI, 2 methods were used: the Gaussian method (Streutker, 2002), and the quantile method (Flores, 2016). Both methods use data from remote sensing of monthly LST and annual product of land cover type (Land Cover Type) at 0.05° resolution, obtained from the MODerate resolution Imaging Spectroradiometer (MODIS) sensor on board the TERRA and AQUA satellite. The SUHI diurnal, obtained with the quantile method in the AMC, shows the maximum value ​​in April (5,28°C) and minimum ​​in August (4,04°C), and the SUHI nocturnal obtained present maximum value in April (2,56°C) and the minimum in December (1,91°​C). However, the SUHI diurnal in the AMS, shows the maximum value ​​in December (5,96°C) and minimum ​​in June (1,38°C), and the SUHI at night present maximum value ​​in October (2,90°C) and minimum ​​in July (1,75°C).